PERKEMBANGAN BUDAYA POPULER JEPANG MELALUI COOL JAPAN DAN DAMPAKNYA TERHADAP KEHIDUPAN SOSIAL DI INDONESIA (STUDI KASUS: KOTA PEKANBARU) - Ningrum, Adystin Widya; Retnaningsih, Umi Oktyari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research is based on the occurrence of a phenomenon in which Japanese popular culture such as manga, anime, and cosplay has experienced an increase in interest in Indonesia over the past years. Various Japanese cultural events often held in various city in Indonesia, including Kota Pekanbaru. This shows how Cool Japan's strategy is successful in promoting Japanese popular culture. With the development of Japanese popular culture in Kota Pekanbaru, of course it has more or less an impact on the social life of the people. This paper shows how the impact caused by the phenomenon of the development of Japanese popular culture in Kota Pekanbaru is. This research uses the perspective of critical theory and the cultural hegemony theory. The method used in this research is descriptive qualitative with observation, interview, and data collection techniques both physical and digital. The results showed that the Japanese popular culture has an impact on hegemony in social life. The high exposure of Japanese popular culture popularity has resulted in increasing enthusiasts to Japanese popular culture, high levels of consumption form a hedonistic or creative lifestyle depending on how to react, s and finally the formation of a community of lovers of Japanese culture Keywords: Japanese popular culture, cultural hegemony, Pekanbaru, Indonesia